2014
DOI: 10.1891/0047-2220.45.4.56
|View full text |Cite
|
Sign up to set email alerts
|

Ex-Offenders in Rural Settings Seeking Employment

Abstract: Rural communities represent unique challenges for the reentering ex-ojfenders. In addition to having access to fewer resources, employment, and limited tax base, rural communities have a unique culture, values, and beliefs that may further increase barriers to employment for ex-offenders. The purpose of this article is to examine characteristics of rural communities that serve as barriers to employment for ex-offenders, to contrast rural and urban issues, and to examine employers' hiring practices in rural com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Another specific type of employment service that yielded significant results was how to keep a job. Previous research indicates that keeping a job and maintaining it can also be a challenge (Atkin & Armstrong, 2013;Ethridge et al, 2014;Garland, Wodahl, & Mayfield, 2010), and has been identified as a much needed service, especially given the strong negative correlation between employment and recidivism for FIPs (Atkin & Armstrong, 2013;Holzer et al, 2007;La Vigne et al, 2008). The results of the present study also reveal that prior to and while in prison, fewer study participants reported that they were utilizing these services but significantly more wanted to utilize these services after release.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Another specific type of employment service that yielded significant results was how to keep a job. Previous research indicates that keeping a job and maintaining it can also be a challenge (Atkin & Armstrong, 2013;Ethridge et al, 2014;Garland, Wodahl, & Mayfield, 2010), and has been identified as a much needed service, especially given the strong negative correlation between employment and recidivism for FIPs (Atkin & Armstrong, 2013;Holzer et al, 2007;La Vigne et al, 2008). The results of the present study also reveal that prior to and while in prison, fewer study participants reported that they were utilizing these services but significantly more wanted to utilize these services after release.…”
Section: Discussionsupporting
confidence: 52%
“…An added impediment to service availability to FIPs here is if there is less revenue and tax dollars to support these programs. Nonurban areas also have lesser access to health care services (Wallace & Papachristos, 2014), reduced employment opportunities (Ethridge, Dunlap, Boston, & Staten, 2014), and service sector jobs that tend to offer low wages and limited benefits (Gibbs, Kusmin, & Cromarite, 2004).…”
Section: Reentry and Type Of Locationmentioning
confidence: 99%
“…However, previous studies have shown that rural residents—including women, specifically—report concerns related to cost of care and uncertainty about insurance coverage (Loftus et al, 2018) and are less likely to receive preventive health care services (Casey et al, 2001; Larson & Correa-de-Araujo, 2006). The lack of service utilization, as well as low rates of employment postrelease, may thus be a result of challenges particular to rural justice-involved women reentering their communities, including fewer available health care providers, employment opportunities, or transportation resources (Ethridge et al, 2014; Ward, 2015; Wodahl, 2006; Zajac et al, 2014). These challenges may in part explain the differences in RHI-C scores between the present sample and samples of college students or adults receiving behavioral health services, in that the rural context may make connections to community institutions more challenging, but may also exacerbate the stigma of previous incarceration or substance use (particularly among women) within small and close-knit social networks (Beichner & Rabe-Hemp, 2014; Buer et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, factors predicting recidivism are known to differ by urban or rural region (Webster et al, 2015), suggesting that they exhibit distinct reentry needs and challenges. For example, employment, despite being an important factor in successful reentry (Bunting et al, 2019; O’Brien & Bates, 2005), may be difficult to obtain in rural areas with fewer, or less remunerative, jobs (Ethridge et al, 2014). Furthermore, limited transportation (Bohmert, 2016; Zajac et al, 2014) and geographically dispersed services may create difficulty for individuals seeking physical or behavioral health care during reentry (Ward, 2015; Wodahl, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, rural and urban differences may affect employment opportunities post-release. While both have similar rates of unemployment, rural communities have been found to have lower wages than urban communities and be more resource strained for provision of reentry services (Ethridge, Dunlap, Boston, & Staten, 2014; Wodahl, 2006).…”
Section: Previous Researchmentioning
confidence: 99%